2016
DOI: 10.1016/j.geoderma.2015.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of addition of HPBCD on diuron adsorption–desorption, transport and mineralization in soils with different properties

Abstract: The influence of different soil properties on diuron adsorption, and the effect of hydroxypropyl-β-Cyclodextrin (HPBCD) on its desorption, leaching and mineralisation have been investigated. The significant variables on adsorption were organic matter (OM) content, aluminum oxides and clay fraction. Diuron desorption from soils presents negative hysteresis when HPBCD solutions were used as an extractant, in comparison to the positive hysteresis when using Ca(NO 3) 2 solutions. Therefore, higher amounts of Diuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…For a specific pesticide, when hydrophobic bonds are the only factor responsible for its adsorption, the K foc values should be relatively constant among the different soils. However, the values obtained in this study are quite different (Table 3), ranged from 7332 to 14263, indicating that the adsorption mechanism is related to some other soil properties in addition to the OC content (Morillo et al, 2002;Undabeytia et al, 2011;Rubio-Bellido et al, 2016). Morillo et al (2000) observed that GPS adsorption to three soils of different characteristics was not related to their CEC and clay mineral content, but to levels of iron and aluminium amorphous oxides and organic matter.…”
Section: Gps Adsorption-desorption On Soilsmentioning
confidence: 58%
“…For a specific pesticide, when hydrophobic bonds are the only factor responsible for its adsorption, the K foc values should be relatively constant among the different soils. However, the values obtained in this study are quite different (Table 3), ranged from 7332 to 14263, indicating that the adsorption mechanism is related to some other soil properties in addition to the OC content (Morillo et al, 2002;Undabeytia et al, 2011;Rubio-Bellido et al, 2016). Morillo et al (2000) observed that GPS adsorption to three soils of different characteristics was not related to their CEC and clay mineral content, but to levels of iron and aluminium amorphous oxides and organic matter.…”
Section: Gps Adsorption-desorption On Soilsmentioning
confidence: 58%
“…HPBCD addition (Figure 5B) provoked a significant decrease of 25 days in the acclimation period (from 79 days for TME to 54 days for TME + HPBCD) (Table 6) in relation to the mineralization in the absence of HPBCD, although a similar global extension of mineralization and mineralization rate was determined (33.9 and 1.00% day –1 , respectively). The explanation for this reduction is the higher bioaccessibility of PYR after HPBCD application due to an increase of its bioavailable fraction just from the beginning of the assay (Reid et al, 2000), reaching a similar global extension of mineralization corresponding to the global PYR bioavailable fraction in soil (Rubio-Bellido et al, 2016). These results also reveal that the increase of PYR bioavailability due to HPBCD addition has no toxic effects on the indigenous microbiota.…”
Section: Resultsmentioning
confidence: 99%
“…Major portion of the pesticides reaches the nontarget regions in the ecological setting either through spray drifting, run off and percolation (Singh and Cameotra, 2013). Pesticides' adsorptive and persistence characteristics often determine their distribution in the environmental compartments (Yue et al, 2017;Rubio-Bellido et al, 2016). Soils have been characterized with severe pollution problems especially due to agrochemicals use in the agricultural regions.…”
Section: Resultsmentioning
confidence: 99%